Guest Covalent Capture by a Host: A Biomimetic Strategy for the Selective Functionalization of a Cavity. Issue 2 (20th November 2012) - Menard, Nicolas; Reinaud, Olivia; Colasson, Benoit
Abstract A biomimetic strategy for the monofunctionalization of a calix[6]arene core is described. It is based on host–guest chemistry (mimicking the Michaelis–Menten adduct in enzymes) and allows the finely tuned pre‐organization of the substrate (an alkyne) with respect to the reactant (three azido groups introduced at the calixarene large rim). It is shown that the thermal Huisgen reaction implemented in this work proceeds under very mild conditions with total regioselectivity of the cycloaddition process. The scope of the reaction was explored and the results suggest that such a supramolecular strategy is quite versatile and could be applied to the selective functionalization of other cavitands bearing different recognition patterns. A detailed structural, thermodynamic, and kinetic study is also reported, highlighting interesting biomimetic features: The importance of the host–guest adduct strength, the high sensitivity of the reaction to the pre‐organization of the reactive partners (alkyne vs. azide), and a significant impact of the embedment on the transition state. The self‐coordination of the monofunctionalized products was also studied and an "endo/exo" switch of the internal side‐chain could be triggered by adding competitive ligands.